Around an Andean Story: The Ukumari - Cipolletti, María Susana (1983)
In addition to the usual problems posed by the analysis of the distribution of a given narrative, in the case of ukumari or ukuku (Quechua names for the bear), there are other facts: while on the one hand there is a narrative current imported from Europe, on the other there are stories collected in various areas of South America that differ in part from that.